The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Verso, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Women artists in history: from antiquity to the 20th century - Slatkin, Wendy (Prentice-Hall, 1985)
"The careers and accomplishments of women creators in Western Civilization are described in an accessible and informative mattner in the Second Edition of Women Artists in History: From Antiquity to the 20th Century. Over sixty artists, mostly painters and sculptors, are featured in this book. Selections were based on each woman's unique and important contributions to the history of art. each artist measures up to the same rigorous standards applied to male artists in other survey texts. To understand and appreciate the achievements of these outstanding women, this volume takes a thorough look at the cultural environment in which they lived and worked, as well as the social, economic, and demographic factors that influenced their art." –From back cover
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Maitresses de maison, maitresses d'ecole: femmes, famille et education dans l'histoire du Quebec - Fahmy-eid, Nadia; Barry, Francine (Boréal Express, 1983)
Recueil de quatorze études, par douze spécialistes, sur des aspects des rapports entre les femmes et l'éducation, et les femmes et la famille à diverses époques de l'histoire du Québec. Un bilan des recherches sur les questions précède ces études.
Keywords: 1600-1699; 1700-1799; 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; his4523; histoire; histoire des femmes*; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; éducation

Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Harper & Row, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques

Un choix sans equivoque : recherches historiques sur les relations amoureuses entre les femmes : XVIe-XXe siecle - Bonnet, Marie-Jo (Denoël, 1981)
C'est le fruit de recherches menées pour une thèse de doctorat de 3e cycle. Etude détaillée, même érudite, mais de lecture facile. Importante bibliographie.
Section: 293 pages
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; LGBTQIA2+; amour lesbien; approches et analyses; cours; discipline; discours dominant; his4860; histoire; histoire de la sexualité; histoire des femmes*; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexologie; sexualité; sexualité lesbienne; sexualités dissidentes; systèmes d'oppressions; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques